Sensitivity and accuracy of refractive index retrievals from measured extinction and absorption cross sections for mobility-selected internally mixed light absorbing aerosols. Issue 9 (1st September 2020) - Cotterell, Michael I.; Szpek, Kate; Haywood, Jim M.; Langridge, Justin M.
Abstract: Aerosol refractive index (RI) is related to particle composition and density, is used in optical spectroscopy studies to probe aerosol physiochemical properties during chemical reactions and gas-particle partitioning, and is important in atmospheric physics. Indeed, aerosol radiative forcing calculations require accurate descriptions of the real ( n ) and imaginary ( k ) RI components and their dependence on wavelength, humidity and particle mixing state. Using cavity ring-down spectroscopy (CRDS) and photoacoustic spectroscopy (PAS) to measure the extinction and absorption cross sections for mobility-selected aerosols is recognized as a good approach to retrieving n and k accurately. However, little work has assessed rigorously the sensitivity and accuracy of the retrieved values from this approach. This work investigates RI retrievals from CRDS- and PAS-measured optical properties for mobility-selected aerosols composed of ammonium sulfate (non-absorbing), nigrosin (strongly light absorbing) or a mixture of these two species. Importantly, we assess the sensitivity in our RI retrievals and then apply a Monte Carlo error propagation analysis to quantify the retrieval accuracy. Our Monte Carlo analysis is the first to account for the full range of uncertainties involved in RI retrievals from optical measurements on mobility-selected aerosol. We also report the first experimental validation of predictive RI mixing rules for non-aqueous internally mixed light absorbing aerosols by comparing mixing rule predictions with measurements for aerosol composed of internal mixtures of ammonium sulfate and nigrosin. The commonplace volume fraction mixing rule fails to predict refractive indices accurately and mixing rules with a physical basis must be used.